The future of social care funding: who pays?*. (6th December 2016) - Kenny, T.; Barnfield, J.; Daly, L.; Dunn, A.; Passey, D.; Rickayzen, B.; Teow, A.
Abstract: With the UK population ageing, deciding upon a satisfactory and sustainable system for the funding of people's long-term care ( LTC ) needs has long been a topic of political debate. Phase 1 of the Care Act 2014 ("the Act") brought in some of the reforms recommended by the Dilnot Commission in 2011. However, the Government announced during 2015 that Phase 2 of "the Act" such as the introduction of a £72, 000 cap on Local Authority care costs and a change in the means testing thresholds 1 would be deferred until 2020. In addition to this delay, the " freedom and choice " agenda for pensions has come into force. It is therefore timely that the potential market responses to help people pay for their care within the new pensions environment should be considered. In this paper, we analyse whether the proposed reforms meet the policy intention of protecting people from catastrophic care costs, whilst facilitating individual understanding of their potential care funding requirements. In particular, we review a number of financial products and ascertain the extent to which such products might help individuals to fund the LTC costs for which they would be responsible for meeting. We also produce case studies to demonstrate the complexities of the care funding system. Finally, we review the potential impact on incentives for individuals to save for care costs under the proposed new means testing thresholds and compare these with the current thresholds. We conclude that: ∙ Although it is still too early to understand exactly how individuals will respond to the pensions freedom and choice agenda, there are a number of financial products that might complement the new flexibilities and help people make provision for care costs. ∙ The new care funding system is complex making it difficult for people to understand their potential care costs. ∙ The current means testing system causes a disincentive to save. The new means testing thresholds provide a greater level of reward for savers than the existing thresholds and therefore may increase the level of saving for care; however, the new thresholds could still act as a barrier since disincentives still exist.